雙語教師專業實踐與反思：國小教師實施「沉浸式英語教學」之個案研究 - 吳昀蒨(Yun-Chien Wu); 簡梅瑩(Mei-Ying Chien) (School Administrators, 2023)
To boost international competitiveness of Taiwan, the Executive Yuan announced the Bilingual 2030 policy in 2018. Schools at all lev¬els since then have begun to implement various bilingual education pro¬grams. However, there has been a serious shortage of bilingual teachers in elementary schools. In addition, it is also a challenge for teachers involved in bilingual programs to manage related issues in curriculum planning, teaching methods and evaluation. This case-study was conducted with a bilingual teacher at an elementary school in Taipei City; semi-structured interviews, classroom observations and document collection were used for data collection to explore the training process of a bilingual teacher and the teaching experience of “Immersion English Learning”. The main findings of this study are as follows: 1. The training of bilingual teachers should focus on the oral language skills of trainee teachers as well as en¬hance their professional knowledge of interdisciplinary subjects; 2. The implementatio